Influence of Path-Goal Theory of Leadership Styles and the Moderating Role of Task Structure in Leadership on Teachers’ Satisfaction, Motivation, and Performance - Pacia, Denward R.; Guevarra, Perla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study investigated the influence of path-goal theory of leadership styles and the moderating role of task structure in leadership on teachers' satisfaction, motivation, and performance in the Division of San Pablo City public secondary schools. The research design adopted for this study was a descriptive-correlational study involving survey questionnaires administered to 579 junior high school teachers across 13 public secondary schools. Data analysis utilized mean, standard deviation, Pearson's correlation coefficient, and multiple regression analysis. Findings indicate that teachers perceived their school heads as demonstrating directive, supportive, participative, and achievement-oriented leadership styles. Task structure in leadership was generally perceived favorably. Teachers exhibited moderate job satisfaction, positive work motivation, and very satisfactory performance across various domains. Correlation analysis revealed significant positive relationships between path-goal theory of leadership styles, work motivation, and teachers' performance. However, no significant relationship was found between leadership styles, task structure in leadership, and job satisfaction. Task structure in leadership showed a weak negative correlation with job satisfaction and a moderate negative correlation with aspects of work motivation but no significant relationship with teachers' performance. Regression analysis demonstrated that path-goal theory of leadership styles directly influenced work motivation and teachers' performance, while job satisfaction had a strong baseline level independent of leadership styles. Task structure in leadership moderated the relationship between leadership styles, job satisfaction, and teachers' performance but did not moderate work motivation. This study contributes to understanding leadership practices that positively influence teachers' motivation and performance, offering implications for enhancing school leadership and improving educational quality.